2011
DOI: 10.1111/j.1600-0579.2010.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Reforming dental workforce education and practice in the USA

Abstract: The USA dental education programmes are facing challenges similar to those confronting countries around the globe, particularly amongst the industrialised nations. The purpose of this study was to evaluate the educational programmes of 15 USA dental schools to determine their impact on improving workforce diversity and oral health care access. The study investigates the predictors of public service plans of dental school seniors in Pipeline and non-Pipeline Program dental schools. We analysed baseline and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…To contextualize this project, and the hypotheses to be tested, it is necessary to provide an account of the changes that have recently been instigated to “modernize” medical and dental training. This account is based on experiences in the United Kingdom but similar restructuring has occurred worldwide (Cooke et al, ; Davidson et al, ; Virdi, ).…”
Section: Introductionmentioning
confidence: 99%
“…To contextualize this project, and the hypotheses to be tested, it is necessary to provide an account of the changes that have recently been instigated to “modernize” medical and dental training. This account is based on experiences in the United Kingdom but similar restructuring has occurred worldwide (Cooke et al, ; Davidson et al, ; Virdi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results from another study showed that education debt has only a small overall effect on specialty choice. 19 Investigators also have analyzed the potential of dental school debt to influence dentists' career choices, [20][21][22][23] including Medicaid participation or practice ownership. 24, 25 Nicholson and colleagues 26 concluded that dentists with high education debt were more likely to enter private practice and work longer hours.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In our previous research, we conducted a baseline and impact analysis to investigate the significant factors associated with plans to care for more underserved minority patients using ADEA senior survey data from 2002-03 and 2006-07. 7,8,13,14 Race/ethnicity and parental income both increased the odds that senior dental students planned to care for minority patients. Specifically, compared to white graduating seniors, URMs were three times more likely (OR=3.23, p<.001) to plan to care for minorities, and Asian/Pacific Islanders were almost two times (OR=1.88, p<.001) more likely to plan to care for minorities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Increasing access to loan repayment programs through better financing is an incremental policy approach to improve short-term access and should be examined more closely in a cost-effective analysis to quantify the gain in access. 14 More worry about debt upon graduation was associated with increased likelihood that students planned to serve minorities. Those planning to provide more care to minority patients may be especially concerned that their choice of service will make it especially difficult to repay their debt.…”
Section: Summary and Implicationsmentioning
confidence: 99%